INDUSTRI GALANGAN KAPAL TRADISIONAL DI BAGANSIAPIAPI - Nofrizal, Nofrizal; Ahmad, Muchtar; Syaifuddin, Syaifuddin (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
Base on the survey and field visiting at the industry location, the state of traditional dockyardindustry in Bagansiapiapi is reported. Traditional dockyards use wood as raw materials for buildingsmall boat of less than 5 GT for cargo or passenger as well as fishing boats. The location of dockyard isbuilt open on the bank of riverine in the coastal area without any covered building. Even facilities in thetraditional dockyard as well as the way to the location are almost no any infrastructure to support it. Thedockyard persists on the wetland environment, swampy area, and unhealthy working condition. Themanagement of the dockyard is family wise as it belong to the one core family, but the boat craftmenmostly extent family. While the technology used mostly is not deliberately heritage from their ancient orotherwise from the long experiences working in the dockyard for many years. The main problem of thetraditional dockyard is the raw wood materials are scare so that difficul to get with high costly price,whilst capital to secure matereials stock unavailable. The consequence, three of four traditional dockyartsurveyed have already or stopping to product a new boat and frustrating to pace the future. The probableeffective idea way out of the situation is to use alterentive boat substitute material such as FRP. Thisidea will be verified by following studies on modern dockyard producing small boat with using alterna-tive non-wood material. It is necessary as a reference for the transformation of the traditional dockyardinto the modern one.